Impact of wearing a surgical mask on respiratory function in view of a widespread use during COVID-19 outbreak. A case-series study: Respiratory Protective Devices fitness for use - Ciocan, Catalina; Clari, Marco; Fabbro, Donatella; De Piano, Maria Luigia; Garzaro, Giacomo; Godono, Alessandro; Gullino, Attilia; Romano, Canzio (La Medicina del Lavoro, 2020)
Background: Because of the COVID-19 outbreak, the widespread use of Respiratory Protective Devices (RPD) is recommended to prevent the spread of infection. This recommendation involves not only healthcare workers but other category of workers and the general population as well, in public places, especially where social distancing is difficult to maintain. The use of facemasks should not cause physical impairment to individuals, especially for people suffering from lung and heart diseases. Objectives: To evaluate the impact of RPDs on the respiratory function in healthy and asthmatic subjects, in order to identify the fitness for use mainly, but not only for, occupational purposes during COVID-19 outbreak. Methods: Ten individuals were included, three of which affected by asthma and three current smokers. A Respiratory Functional Test (RFT) was performed at three times: at the beginning of the work shift 1) without wearing and 2) wearing surgical masks, and 3) after 4 hours of usual working activities wearing the masks. Arterial Blood Gas (ABG) samples were also tested before the first test and the third test. Results: Observed RFTs and ABG parameters did not suffer significant variations, but for Maximal Voluntary Ventilation (P=0.002). Data on asthmatic subjects and smokers were comparable to healthy subjects. Discussion: Our results suggest that wearing a surgical mask does not produce significant respiratory impairment in healthy subjects nor in subjects with asthma. Four hours of continuing mask-wearing do not cause a reduction in breathing parameters. Fitness for use in subjects with more severe conditions has to be evaluated individually. Our adapted technique for RFTs could be adopted for the individual RPDs fitness evaluation.